Systematic Interpretation Of Silicified Specimens of Upper Cretaceous Echinocorys ex. gr. scutata (Leske, 1778), Farokhi Formation, Central Iran - M. Allameh; M. Taherpour Khalil Abad (Journal of Sciences, Islamic Republic of Iran)
Echinocorys ex. gr. scutata is one of the most important echinids in the Upper Cretaceous deposits. In this regard, a stratigraphic section of the Farokhi Formation in the Central Iran is sampled. This formation is less known and described in the geology of Iran. According to the macropaleontological investigations, 1 genus and 1 specious of completely silicified Echinocorythidae are determined and described. In these investigations, the samples are regarded also from the statistical point of view.